Implications of a Remote Study of Children With Cerebral Visual Impairment for Conducting Virtual Pediatric Eye Care Research: Virtual Assessment Is Possible for Children With CVI - Almagati, Reem; Kran, Barry S. (Frontiers in Human Neuroscience, 2021)
The Pandemic of 2020 impacted conducting in-person research. Our proposed project already had an asynchronous online component but was later morphed to add a synchronous online component, thereby eliminating the need for in-person assessment. The project compares the results of various tests between a group of children with Cerebral Visual Impairments (CVI) (N = 4) and an age-matched sample of children without CVI (N = 3) from a pediatric low vision clinic. This model was trialed with a small convenient sample of typically developing children in the same age range (N = 4). Given the positive feedback, recruitment for the larger study was done via encrypted e-mail rather than through traditional mailing. The asynchronous components included recruitment, pre-assessment information, the Flemish CVI questionnaire, Vineland-3 comprehensive parent questionnaire for assessment of age equivalent, and vision function tests such as contrast sensitivity. The synchronous components were administered via Zoom telehealth provided by necoeyecare.org and included assessment of visual acuity via FrACT electronic software and assessment of visual perceptual batteries via the CVIT 3-6. Our virtual testing protocol was successful in the seven participants tested. This paper reviews and critiques the model that we utilized and discusses ways in which this model can be improved. Aside from public health considerations during the pandemic, this approach is more convenient for many families. In a broader perspective, this approach can be scaled for larger N studies of rare conditions such as CVI without being confined by proximity to the researcher.